1921
DOI: 10.1037/h0071479
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Associative Inhibition.

Abstract: Strike out with a cross mark thus, X, the false capital that you have just learned.Make no other marks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1931
1931
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…result of divided paths but has some deeper basis yet unknown" (p. 311). Kline (1921) used 'meaningful' material (states and capitals, counties and county seats, and books and authors) in a study of interference effects of associations. He found that if the first associative bond had a recall power of 10 percent or less it facilitated the second association, if it had a recall power of 15 percent to 40 percent the inhibitory power was small, if it had a recall power of 45 percent to 70 percent the inhibiting strength approached a maximum, if the recall power was 70 percent to 100 percent the inhibition was of medium strength and in some cases might disappear or even facilitate the learning of a new association.…”
Section: Introductionmentioning
confidence: 99%
“…result of divided paths but has some deeper basis yet unknown" (p. 311). Kline (1921) used 'meaningful' material (states and capitals, counties and county seats, and books and authors) in a study of interference effects of associations. He found that if the first associative bond had a recall power of 10 percent or less it facilitated the second association, if it had a recall power of 15 percent to 40 percent the inhibitory power was small, if it had a recall power of 45 percent to 70 percent the inhibiting strength approached a maximum, if the recall power was 70 percent to 100 percent the inhibition was of medium strength and in some cases might disappear or even facilitate the learning of a new association.…”
Section: Introductionmentioning
confidence: 99%
“…The only conclusion was stated thus: "We have found then that in acquiring associations there is involved an inhibitory process which is not a mere result of divided paths but has some deeper basis yet unknown" (p. 311). Kline (1921) used 'meaningful' material (states and capitals, counties and county seats, and books and authors) in a study of interference effects of associations. He found that if the first associative bond had a recall power of 10 percent or less it facilitated the second association, if it had a recall power of 15 percent to 40 percent the inhibitory power was small, if it had a recall power of 45 percent to 70 percent the inhibiting strength approached a maximum, if the recall power was 70 percent to 100 percent the inhibition was of medium strength and in some cases might disappear or even facilitate the learning of a new association.…”
Section: Introductionmentioning
confidence: 99%
“…The acquisition of practical skills leads to a decrease in the effect of interference (e.g., Kline, 1921;Stroop, 1992). Therefore, we compared the results of the learning blocks performed by the subjects of the experimental and control groups.…”
Section: General Psychologymentioning
confidence: 99%